Roles and challenges of community health volunteers in community midwifery practice in Siaya county, kenya - Syagga, Edwinah A.; Estambale, Benson B. (Numid Publishers, 2017)
Introduction: One of the objectives of the United Nations Millennium Development Goals (MDGs) was to reduce MMR by an average of 5.5% every year over the period between1990–2015. As a result, the first international meeting focusing on scaling up of the midwifery workforce at community level, drafted a Call to Action for all countries with high Maternal Mortality Rate to embark on intensified action to scale up midwifery care at the community level (Health 2005). Community health volunteers have been increasingly recognized as integral members of primary health care teams, especially in poor and underserved communities. The objective of this study was to evaluate the effectiveness of the community health volunteers in the promotion of skilled birth attendance in the Community Midwifery model of care in Siaya County. Methods: This was a cross-sectional study that used both quantitative and qualitative data in six sub-counties of Siaya County. The study involved facilities as well as sampled community women who had given birth within the previous year and who were served by the four sampled health facilities. It also involved skilled birth attendants working at the health care facilities of the primary levels of the health care system as well as the CHVs attached to the selected health care facilities. Findings: The community midwifery model used in Siaya was not the one stipulated in the guidelines issued by the Division of Reproductive Health. However, the model used the CHVs for its effectiveness. Conclusion and Recommendations: The CHVs are effective in community midwifery practice
Keywords: Community midwifery; Community health volunteers; Skilled birth attendance; Sustainability